The Relationship Among Exclusive Breastfeeding, Complementary Feeding (MP-ASI), and Infectious Diseases in Children Aged 7 to 24 Months - Aliyah Rosalina; Tonny Cortis Maigoda; Emy Yuliantini (Poltekkes Kemenkes Palu, 2023)
Stunting is the state of height of a person, not by age. Numerous risk factors, such as complementary feeding, viral illnesses, and exclusive breastfeeding, contribute to the high prevalence of stunting. Breast milk consists of fats, carbohydrates, calories, proteins, and vitamins that can support the development and growth of a healthy child. Complementary feeding must be adequate, nutritious, and appropriate in the type, time, frequency, portion, and menu variations in addition to breast milk. These variations that are not quite right will cause growth failure and infectious diseases. This study aimed to ascertain the relationship between exclusive breastfeeding, complementary feeding, infectious diseases, and the incidence of stunting in children between the ages of 7 and 24 months at the Sawah Lebar Health Center in Bengkulu City in 2023. This study used a cross-sectional method. The population in this study were all children aged 7-24 months in Sawah Lebar Public Health Center, while the sample for this study was 52 people taken by random sampling. The study finds a relationship among exclusive breastfeeding, complementary feeding, infectious diseases, and the prevalence of stunting in children aged 7 to 24 months at the Sawah Lebar Public Health Center in Bengkulu City with a p-value (<0,05). This study is recommended to continue by adding any variable such as a variety menu, texture, and appropriate time giving complementary feeding.